Pengaruh Edukasi Perawatan Kaki Menggunakan Media Video Terhadap Perilaku Pencegahan Terjadinya Luka Diabetik pada Pasien Diabetes Militus - Apriani, Desi; Saputra, Bayu; Roslita, Riau (Jurnal Kesehatan Komunitas, 2024)
Diabetes Mellitus (DM) occurs due to high blood sugar levels which can cause various complications. A chronic complication of DM in Indonesia is 15% diabetic foot. The role of education is very important to prevent the risk of diabetic wounds. This study aimed to determine the effect of providing foot care education with video media on the prevention of diabetic wounds in type 2 DM patients. The design of this study was pre-experimental with the type of One-group pretest-posttest design. The sample of this study amounted to 33 people with the Probability Sampling technique. The research instrument was a questionnaire sheet. The results of the univariate analysis were dominated by female respondents, average age 49.52 years, high school education level (48.5%), and household work (51.5%). The behavior of respondents before and after being given education using video has increased namely the mean knowledge value from 7.91 to 9.97, the mean attitude value from 29.67 to 31.73, and the mean value of action from 6.30 to 7.97. The results of the bivariate analysis could conclude that there was an effect of foot care education on the behavior of preventing diabetic wounds in type 2 DM patients. This study suggests to Payung Sekaki Health Center that foot care education with video media can be given to DM patients.